Melatonin Promotes Nerve Regeneration Following End-to-Side Neurorrhaphy by Accelerating Cytoskeletal Remodeling via the Melatonin Receptor-dependent Pathway - Liu, Chiung-Hui; Chang, Hung-Ming; Yang, Yin-Shuo; Lin, Yu-Ta; Ho, Ying-Jui; Tseng, To-Jung; Lan, Chyn-Tair; Li, Shao-Ti; Liao, Wen-Chieh (Neuroscience, 2020)
•Melatonin suppresses activation of calmodulin-dependent protein kinase II (CaMKII) in sprouting axons.•Melatonin regulates cytoskeleton rearrangement via a membrane receptor pathway in neural cells.•Melatonin at physiological concentrations (1–10 nM) causes cytoskeletal changes in regenerated axons. Acceleration of cytoskeletal remodeling in regenerated axons is crucial for a fully functional recovery following peripheral nerve injury (PNI). Melatonin plays important roles in cell differentiation and protection of cytoskeleton stability, thus, the present study aimed to investigate whether melatonin can enhance neurite outgrowth and promote cytoskeletal remodeling in a PNI animal model and in differentiated neurons. End-to-side neurorrhaphy (ESN) rat model was used for assessing cytoskeletal rearrangement in regenerated axon. Subject rats received 1 mg/kg/day melatonin injection for one month. The amplitude of compound muscle action potentials and the number of re-innervated motor end plates on target muscles were assessed to represent the functional recovery after ESN. Melatonin treatment enhanced functional recovery after ESN, compared to the saline treated group. Additionally, in spinal cord and peripheral nerve tissue, animals receiving melatonin displayed enhanced expression of GAP43 and β3-tubulin one month after ESN, and an increased number of re-innervated motor end plates on their target muscle. In vitro analysis revealed that melatonin treatment significantly promoted neurite outgrowth, and increased expression of melatonin receptors as well as β3-tubulin in mouse neuroblastoma Neuro-2a (N2a) cells. Treatment with a melatonin receptor antagonist, luzindole, significantly suppressed melatonin receptors and β3-tubulin expression. Importantly, we found that melatonin treatment suppressed activation of calmodulin-dependent protein kinase II (CaMKII) in vitro and in vivo, suggesting that the β3-tubulin remodeling may occur via CaMKII-mediated Ca2+ signaling. These results suggested that melatonin may promote functional recovery after PNI by accelerating cytoskeletal remodeling through the melatonin receptor-dependent pathway.